Supplementation of Direct Fed Microbial (DFM) on in vitro Fermentability and Degradability of Ammoniated Palm Frond - Suryani, Heni; Zain, M.; Ningrat, R.W.S.; Jamarun, N. (Pakistan Journal of Nutrition, 2015)
This study was conducted to determine the effect of Direct Fed Microbial (DFM) supplementation on in vitro fermentability and degradability of ammoniated palm frond. DFM’s used were Saccharomyces cerevisiae (SC), Aspergillus oryzae (AO) and Bacillus amyloliquefaciens (BA). Palm frond previously treated with 6% urea. The treatments were of, P0 = ammoniated oil palm frond, P1 = P0+SC (1% DM), P2 = P0+AO (1% DM), P3 = P0+BA (1% DM), P4 = P0+SC+AO (1% DM), P5 = P0+SC+BA (1% DM), P6 = P0+AO+BA (1% DM), P7 = P0+SC+AO+BA (1% DM). Variables measured were Dry matter (DM) and Organic matter (OM) in vitro digestibility, concentration of Ammonia (NH3), Volatile Fatty Acid (VFA) and fluid ruminal pH values as fermentability indicators. Data were analyzed using analysis of variance (ANOVA) and difference among means were tested using LSD. The results showed that the supplementation of DFM were significantly (p0.05) on fluid ruminal pH values. Digestibility of DM and OM increased from 47.5% (without DFM) to 51.55% (with DFM), 48.89 to 52.41%. The concentration of NH3-N and VFA increased from 12.28 to 14.28 mM and 108.35 to 125.90 mM, respectively. The rumen pH with supplementation of DFM is relatively more stable. The results showed that SC was suitable to be used single or in combination with AO or BA, but the combination of SC+BA (P5) give the best results on digestibility of DM, OM, concentration of NH3-N and VFA.